Factors impacting consumer's fairness perception in a dynamic pricing context: a systematic literature review. (30th March 2023) - Diaz, Christian; Avella, Antonella; Jr., Jose R. Vera; Neubert, Michael
Since dynamic pricing (DP) is expected to become the future of pricing strategies, it is important to uncover the different factors associated to its perceptions among consumers. The purpose of this systematic literature review is to answer the research question about what are the factors that influence consumer perception of pricing fairness in a DP context. The synthesis section covered 45 articles, which discovered three research streams identified as consumer-based, company-based, and environmental-based. This systematic literature review proposes seven calls for further research, for instance, a call for a quantitative assessment of the collective impact of the different factors in the perception of fairness in a DP context. The findings of this research contribute to scholars by synthesising the current body of knowledge and suggesting new areas of study. It also offers managers practical models that aim to integrate perception factors to serve as the basis for successful DP strategies.